2017
DOI: 10.1017/s0025100317000238
|View full text |Cite
|
Sign up to set email alerts
|

Complementary length in vowel–consonant sequences: Acoustic and perceptual evidence for a sound change in progress in Bavarian German

Abstract: This study is concerned with the Bavarian German dialect feature of complementary length in vowel plus consonant sequences according to which tense (long) vowels always precede lenis stops (short closure) and lax (short) vowels always precede fortis stops (long closure). The study investigates whether a vowel length contrast is developing before fortis stops due to dialect leveling. We measured vowel and consonant duration in trochaic words differing only in vowel length which were read by 40 older and younger… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
27
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(37 citation statements)
references
References 30 publications
(41 reference statements)
6
27
2
Order By: Relevance
“…It has been found that the percentage of fused responses is higher when stimuli are voiced than when they are voiceless (McGurk & MacDonald, 1976;Sekiyama & Tohkura, 1991) (but see Sekiyama et al (1995) for a reversed finding); percentage of fused responses is highest for plosive stimuli, intermediate for fricatives and lowest for sonorants (Sekiyama et al, 1995;Massaro & Cohen, 1995) (but see Paré et al (2003) for a reversed finding). Knowing that the arisal of the McGurk effect strongly depends on the temporal synchronization of the articulatory and the auditory signal (Hertrich et al, 2009), these findings make perfect sense as different manners of articulation, as well as voicing change the temporal patterns of the speech signal (for complementary vowel length see Kleber, 2017).…”
Section: Distributional Properties Of Physical Cuesmentioning
confidence: 95%
“…It has been found that the percentage of fused responses is higher when stimuli are voiced than when they are voiceless (McGurk & MacDonald, 1976;Sekiyama & Tohkura, 1991) (but see Sekiyama et al (1995) for a reversed finding); percentage of fused responses is highest for plosive stimuli, intermediate for fricatives and lowest for sonorants (Sekiyama et al, 1995;Massaro & Cohen, 1995) (but see Paré et al (2003) for a reversed finding). Knowing that the arisal of the McGurk effect strongly depends on the temporal synchronization of the articulatory and the auditory signal (Hertrich et al, 2009), these findings make perfect sense as different manners of articulation, as well as voicing change the temporal patterns of the speech signal (for complementary vowel length see Kleber, 2017).…”
Section: Distributional Properties Of Physical Cuesmentioning
confidence: 95%
“…A subset of the children's data was compared to the production data of a group of ten young adults (8 female) from the same regional area (Munich and surrounding areas) that were obtained for a previous study [14]. In this study speakers were asked to read out loud a total of 10 times 46 different words each presented in isolation and in randomized order on a computer screen in a moderate voice and tempo.…”
Section: Speakers and Experimental Designmentioning
confidence: 99%
“…The continnuum used for this perception experiment was taken from a previous study on the perception of the combined vowel length and voicing contrast in German [14] and slightly modified for the current study. Originally, the continuum spanned the words Hagen (/ha:g@n/, the name of a German city and a male name) to Haken to hacken.…”
Section: Stimuli and Experimentsmentioning
confidence: 99%
See 2 more Smart Citations